Survival and prognostic factors in rhino-orbito-cerebral mucormycosis: A 3-year cohort study - Zahra Zia; Mohamad Javad Sajadi; Hanieh Bazrafshan; Behzad Khademi; Masoud Janipour (Scientific Reports)
Abstract Mucormycosis, a severe fungal infection, has exhibited a concerning increase in recent years, particularly during the COVID-19 outbreak. This three-year cohort study aims to investigate an overview of the epidemiology, clinical and radiographic signs, treatment, and prognosis of Rhino-Orbito-Cerebral Mucormycosis (ROCM). This prospective cohort study was conducted from 2019 to 2022 at Khalili Hospital in Shiraz, Iran. It focused on proven cases of ROCM. Patients underwent a stepwise treatment protocol, with meticulous documentation of findings from ophthalmological examinations and imaging studies. Additionally, a three-year follow-up period was implemented to monitor patient progress and assess the effectiveness of treatment strategies. Statistical analyses were performed using IBM SPSS statistics. In this study, 77 patients with ROCM participated. Most patients presented with facial pain (75.3%), swelling (62.3%), and vision loss (51.9%). Treatment included combined antifungal therapy and surgical debridement, with 7.8% undergoing ocular exenteration. Notably, despite the extensive disease, all cases that underwent orbital exenteration survived during the 3-year follow-up. Impaired V2 nerve function was associated with higher mortality rates, and patients presenting with an initial visual acuity of No Light Perception (NLP) had higher mortality compared to those with other degrees of visual impairment. The convergence of mucormycosis, specifically in the form of ROCM, with COVID-19 has led to an outbreak characterized by high mortality and morbidity rates. This cohort study meticulously documented the long-term follow-up of these patients, aiming to provide novel insights into the epidemiology, clinical and radiographic signs, treatment, and prognosis of this fungal infection.